EVOLUTION OF THE SAIVAL GRANITIC STOCK ROCKS FROM TRÊS CORREGOS BATOLITH, SOUTH OF SÃO PAULO STATE - Vieira, Otávio Augusto Ruiz Paccola; Godoy, Antonio Misson [UNESP]; Duarte, Nicolli Ochi [UNESP] (UNESP - Universidade Estadual Paulista, 2022)
The Saival Granitic Stock rocks are located in the extreme southwest of São Paulo state, inserted in the Araçaíba Topographic Map region, 1:50.000 scale, in the municipality of Apiaí. The igneous lithotypes are intrusive and associated with the Barra do Chapéu Granite rocks, which are a part of the zone distribution and evolution of the Três Córregos Batholith. They are associated with the Neoproterozoic granite genesis evolution of the Apiaí Terrain. These rocks are intrusive in lithotypes of the Água Clara Formation metavolcanosedimentary unit, of Meso-to Neoproterozoic age of the Açungui Supergroup. The stock rocks are distributed in approximately 65 km², with a slightly elongated shape in the NNE-SSW direction, showing tectonic contacts and marked by the interference of the Conceição do Herval and Barra do Chapéu faults, in addition to Saival fault, in the NW-SE direction. These rocks are characterized by pink porphyritic biotite monzogranite facies, gray inequi-to equigranular monzogranite facies and pink equigranular syenogranite and alkali granite facies, in addition to pegmatitic rocks and late aplites. Chemically, they are high potassium calc-alkaline granitic rocks, predominantly peraluminous. These are I type granites, generated in a syn-to post-collisional environment, from the fusion of rocks from the lower crust and associated with the construction of the Ribeira Magmatic Arc correlated to the collisional event of the Ribeira Orogenesis.
EVOLUÇÃO DAS ROCHAS GRANÍTICAS DO STOCK SAIVAL DO BATÓLITO TRÊS CÓRREGOS, SUL DO ESTADO DE SÃO PAULO
Keywords: Apiaí Terrane; Geochemistry; Mapping; Saival Granite